2021
DOI: 10.3389/fimmu.2021.670646
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Improves Motor Function and Alleviates Neuropathic Pain in Male Mice After Spinal Cord Injury by Inhibiting MAPK Pathway

Abstract: BackgroundTraumatic spinal cord injury (SCI) causes severe motor dysfunction and persistent central neuropathic pain (Nep), which has not yet been effectively cured. Programmed cell death ligand-1 (PD-L1) is typically produced by cancer cells and contributes to the immune-suppressive in tumor microenvironment. However, the role of PD-L1 in regulating inflammatory response and Nep after SCI remains unclear. A growing amount of researches have begun to investigate the effect of PD-L1 on macrophages and microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…3,10,22 In addition, programmed cell death ligand-1 (PD-L1), a factor produced by cancer cells, has been reported in preclinical studies to be involved in analgesia and hyperalgesia processes and regulate neuronal activity. 11,34 Furthermore, although STAMBP, a member of the Jab1/MPN metalloenzyme (JAMM) family of deubiquitinating enzymes (DUBs), 14 has not been directly associated with pain processes in previous research, analysis of the presented data revealed an alteration of STAMBP in patients with knee OA. 24 Previous studies have highlighted the involvement of STAMBP in the regulation of inflammatory cascade by facilitating the maturation of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 64%
“…3,10,22 In addition, programmed cell death ligand-1 (PD-L1), a factor produced by cancer cells, has been reported in preclinical studies to be involved in analgesia and hyperalgesia processes and regulate neuronal activity. 11,34 Furthermore, although STAMBP, a member of the Jab1/MPN metalloenzyme (JAMM) family of deubiquitinating enzymes (DUBs), 14 has not been directly associated with pain processes in previous research, analysis of the presented data revealed an alteration of STAMBP in patients with knee OA. 24 Previous studies have highlighted the involvement of STAMBP in the regulation of inflammatory cascade by facilitating the maturation of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 64%
“…It was in this work found that overexpressed circSMEK1 promotes NP development and spinal cord inflammation in CCI rats. When NP occurs, the phenotypes of microglia usually change, with an increase in pro-inflammatory microglia [ 30 , 31 ]. In this work, it was manifested that overexpressed circSMEK1 increased CD68 expression in CCI rats and LPS-treated microglia while inhibited CD206 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The functional rehabilitation of SCI mice after different treatments was also evaluated by MEP as previously described. [ 42 ]…”
Section: Methodsmentioning
confidence: 99%
“…The functional rehabilitation of SCI mice after different treatments was also evaluated by MEP as previously described. [42] Histological Staining and Immunofluorescence Labeling: At designated times, mice were euthanized and transcardially perfused with saline followed by 4% paraformaldehyde. Then their spinal cords were harvested, fixed by 4% paraformaldehyde, embedded in paraffin, and sectioned into 20 μm thickness.…”
Section: Characterization Of Mex and Meximentioning
confidence: 99%